Neurotherapy : progress in restorative neuroscience and neurology : proceedings of the 25th international summer school of brain research, held at the Royal Netherlands Academy of Arts and Sciences, Amsterdam, the Netherlands, August 25-28, 2008 /: progress in restorative neuroscience and neurology : proceedings of the 25th international summer school of brain research, held at the Royal Netherlands Academy of Arts and Sciences, Amsterdam, the Netherlands, August 25-28, 2008. (2009) - Unknown
No abstract available